“Impact Analysis of Digital Marketing on Dental Health Care Practices in Jaipur, Rajasthan: A Vis a Vis study” - Dr. Vaishali Purohit (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2020)
With the introduction of the first commonly used commercial websites in the 1990s, digital technology brought a new level of convenience to consumers. Digital revolution had altered and admired elemental of commerce and continues to deplete a greater share of the entire marketing budget each year. As digital technologies and artifices derive, this amplitude should continue to hike. While much analysis has been directed on digital marketing, most has been centralized on industries other than dentist healthcare. An aim of dental health advisement is to appraise connections and motivate individuals to pay assiduity to general dental concerns and to choose definite dentists, with best hospital and clinical ableness. Dentists in particular and health care organizations need to familiarize themselves with the most efficacious ways to reach people of all ages. This research endeavor seeks to be one such study by investigating the effectiveness of digital marketing practices particularly in dental practices on the population in the area of Jaipur, Rajasthan. The aim of this research is to provide an understanding of the new and dynamic channels of digital marketing of dental practices directed towards positive marketing outcome which in turn results in successful dental clinics. The survey questionnaire was deployed via an online tool (Google Form) through Survey Monkey and was promoted to 100 respondents’ i.e dentists and dental hospital marketers for three weeks. Various factors of digital marketing and their influence analysis were conducted on respondent’s opinion, which was further statistically analyzed. Significant “p” value postulated that the hypothesis H1: There is a significant relationship between digital marketing and dental practices in Rajasthan was accepted and proved. Finally the research concluded that for dental practices, digital marketing represents an opportunity to engage current and prospective patients more easily than ever before. Practices that incorporate digital marketing such as social media into their marketing efforts will be strategically positioned to grow the business graph of dentists up to apex. Dental practitioners actively use digital marketing and social media for marketing and communication. Thus, this research paper would provide valuable information for decision makers and marketing teams at dental hospitals.